MiR-21-5p/203a-3p promote ox-LDL-induced endothelial cell senescence through down-regulation of mitochondrial fission protein Drp1. (June 2017) - Zhang, Jie-Jie; Liu, Wei-Qi; Peng, Jing-Jie; Ma, Qi-Lin; Peng, Jun; Luo, Xiu-Ju
Graphical abstract: Highlights: Plasma levels of miR-21-5-5p/203a-3p are elevated in hyperlipidemic rats. miR-21-5p/203a-3p are up-regulated in ox-LDL-induced senecent endothelial cells. Drp1 is a direct target for miR-21-5p but not for miR-203a-3p. miR-21-5p/203a-3p enhances mitochondrial dysfunction through down-regulating Drp1. Abstract: This study aims to identify both endothelia-specific/enriched and senescence-associated miRNAs as well as their functions. The rats were fed on high-fat diet to establish a hyperlipidemic model, which showed an increase in plasma lipids and acceleration in endothelial senescence and endothelial dysfunction, accompanied by alterations in 7 endothelia-specific/enriched and senescence-associated miRNAs. Among the 7 selected miRNAs, miR-21-5p and miR-203a-3p were significantly up-regulated in a human umbilical vein endothelial cells (HUVECs) senescent model induced by ox-LDL, consistent with their changes in the hyperlipidemic rats. After performing the bioinformatic analysis, dynamin-related protein 1 (Drp1) was predicted to be a potential target for both miR-21-5p and miR-203a-3p. In ox-LDL-induced senescent HUVECs, Drp1 was significantly down-regulated, concomitant with mitochondrial dysfunctions and the activation of AMPK-p53/p16 pathway, while these phenomena were attenuated by miR-21-5p or miR-203a-3p inhibitor. Luciferase reporter gene assay confirmed a direct interaction between miR-21-5p and Drp1 but not between miR-203a-3p and Drp1. Based on these observations, we conclude that miR-21-5p/203a-3p promote ox-LDL-induced endothelial senescence through down-regulation of Drp1 in a direct or indirect way. Our findings highlight the plasma levels of miR-21-5p/203a-3p may serve as novel biomarkers to evaluate the degree of endothelial senescence in hyperlipidemia.